Radical‐Mediated Acyl Thiol‐Ene Reaction for Rapid Synthesis of Biomolecular Thioester Derivatives. Issue 29 (4th August 2021) - McLean, Joshua T.; Milbeo, Pierre; Lynch, Dylan M.; McSweeney, Lauren; Scanlan, Eoin M.
Abstract: The thiol‐ene 'click' reaction has emerged as a versatile process for carbon–sulfur bond formation with widespread applications in chemical biology, medicinal chemistry and materials science. Thioesters are key intermediates in a wide range of synthetic and biological processes and efficient methods for their synthesis are of considerable interest. Herein, we report the first examples of acyl‐thiol‐ene (ATE) for the synthesis of biomolecular thioesters, including peptide, lipid and carbohydrate derivatives. A key finding is the profound effect of the amino acid side chain on the outcome of the ATE reaction. Furthermore, radical generated thioesters underwent efficient S‐to‐N acyl transfer and desulfurisation to furnish 'sulfur‐free' ligation products in an overall amidation process with diverse applications for chemical ligation and bioconjugation. Abstract : Radical‐mediated acyl thiol‐ene reactions between biologically relevant alkene and thioacid components enables rapid, chemoselective and high yielding thioester formation. This reaction in combination with substrates that enable intramolecular acyl transfer permits access to native and modified products beyond the thioether linkage.